2010
DOI: 10.1007/s11270-010-0362-8
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of Hydroponics Wastewater Using Constructed Wetlands in Winter Conditions

Abstract: Hydroponics culture generates large amounts of wastewater that are highly concentrated in nitrate and phosphorus but contains almost no organic carbon. Constructed wetlands (CWs) have been proposed to treat this type of effluent, but little is known about the performance of these systems in treating hydroponic wastewater. In addition, obtaining satisfactory winter performances from CWs operated in cold climates remains a challenge, as biological pathways are often slowed down or inhibited. The main objective o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
56
1
4

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(61 citation statements)
references
References 24 publications
0
56
1
4
Order By: Relevance
“…Brady et al (1999) highlighted that nitrate leaching from agricultural activities could also cause several environmental problems including the loss of calcium and other cations as well as moving into surface or groundwater where it can severely impact the quality of drinking water. Environmental pollution from hydroponics in terms of nutrients has also been reported by Fernandez (2009) and Gagnon et al (2010). These facts have been supported by a survey carried out during the initial phase of the study whereby it has been found that 300-400 litres of drain out solution (hydroponic effluents) were lost per day from one greenhouse with nitrate values exceeding 50 mg/L (EPA, 1991).…”
Section: Discussionmentioning
confidence: 62%
See 1 more Smart Citation
“…Brady et al (1999) highlighted that nitrate leaching from agricultural activities could also cause several environmental problems including the loss of calcium and other cations as well as moving into surface or groundwater where it can severely impact the quality of drinking water. Environmental pollution from hydroponics in terms of nutrients has also been reported by Fernandez (2009) and Gagnon et al (2010). These facts have been supported by a survey carried out during the initial phase of the study whereby it has been found that 300-400 litres of drain out solution (hydroponic effluents) were lost per day from one greenhouse with nitrate values exceeding 50 mg/L (EPA, 1991).…”
Section: Discussionmentioning
confidence: 62%
“…Thus possibly requiring regulatory measures to be put in place to control the discharge of effluents and mitigate the environmental impacts. Given limited information of the impact of hydroponics effluents, this study focussed [6][7]2017 mainly on a survey conducted around the island to assess hydroponics growers' awareness of the environmental impact associated with the effluents. During the study the area under hydroponics production was around 25 hectares.…”
Section: Introductionmentioning
confidence: 99%
“…It was reported that removal efficiencies for NO À 3 -N and NO À 2 -N increased with C/N ratio [8,20,35]. A significant effect of carbon addition on the nitrate removal was informed for the treatment of nitrate-contaminated wastewater using CWs [8,36,37]. Gagnon et al [37] reported that mean nitrate removal efficiency was just 7% in HSSF CW mesocosms treating hydroponics wastewater without carbon addition, but achieved about 70% in those with sucrose addition at a COD/NO À 3 -N ratio of 3.5:1.…”
Section: Insufficient Carbon Sourcementioning
confidence: 99%
“…A significant effect of carbon addition on the nitrate removal was informed for the treatment of nitrate-contaminated wastewater using CWs [8,36,37]. Gagnon et al [37] reported that mean nitrate removal efficiency was just 7% in HSSF CW mesocosms treating hydroponics wastewater without carbon addition, but achieved about 70% in those with sucrose addition at a COD/NO À 3 -N ratio of 3.5:1. Ingersoll and Baker [20] reported that nearly complete nitrate removal could be achieved at a critical C/NO À 3 -N of around 5:1 in FWS CW microcosms treating nitrate-contaminated wastewater.…”
Section: Insufficient Carbon Sourcementioning
confidence: 99%
“…High yield hydroponic systems require a considerable amount of macro-and micronutrients from industrial and mining origin, leading to high energy (i.e., for production and transport) and finite resources use (e.g., phosphorus and oil) . Also, in no-recirculating systems, intermittent disposal of the considerable amounts of nutrient rich water leads to high water consumption as well as surface and groundwater pollution (Gagnon et al, 2010). The regular exchange of water performed in conventional aquacultural systems is not necessary in aquaponics.…”
Section: Thesis Outlinementioning
confidence: 99%